ANALISIS TINGGI DAN BERAT BADAN ANAK BARU MASUK SEKOLAH SEBAGAI DETEKSI DINI GANGGUAN GIZI PADA ANAK USIA SEKOLAH DASAR - Purnamasari, Dyah Umiyarni; Kusuma Wati, Erna (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT  Height of new children entered primary school can explaine the growth of the previous age which strongly associated with health and nutritional history of the past, while the weight loss associated with nutritional status conditions in the present. The objective of this study was to analyze the new children's height and weight  as early detection of nutritional disorders in school children. This research was explanatory survey with crosssectional approach. Observed variables include height and weight of children  and interpretation of achievement based on the percent of the median, the height for age index, the weight for age index and Bassal Metabolism Index.  The samples are all new children entered school in SDN 1Karangklesem,  numbered of 27 people. The analysis showed an average height attainment of male students is 96.2% of the WHO standard median and 95.1% female students, while achieving an average weight of male students was 93.3% of the median standard WHO and women 78.6%. Based on height for age index,  the nutritional disorder most commonly found is stunted as much as 29.6%, 22,2 % malnutrition by weight for age index and  29,6 % wasted by BMI.  Suggestion to monitor the nutritional status of children  regularly as  malnutrition. Keywords :  School Children, Weight, Height  Kesmasindo  Volume 5( 1)  Januari 2012, hlm. 12-22